Discourse Network Analysis of CNN’s “Indonesia Gelap”: Advocacy Coalition and Public Sphere - Bakry, Gema Nusantara; Rahman, Azizul; Ramadhan, Muhamad Harikal (Jurnal Kajian Jurnalisme, 2025)
Demonstrations in Indonesia frequently reflect students’ social and political actions, particularly in criticizing government policies. In exploring the phenomenon of “Demo Indonesia Gelap,” this study uncovered patterns of public discourse through the Advocacy Coalition Framework (ACF) and Habermas’ concept of the public sphere. It analyzed how CNN Indonesia framed the demonstration and assessed whether its coverage adhered to principles of independent journalism. Using discourse network analysis, this research identified the roles played by relevant actors, including students, academics, and media outlets, in shaping public opinion. Findings indicate that students remain central in mobilizing critical discourse against government policies, while the media significantly influences the narratives surrounding such demonstrations. Although CNN Indonesia effectively disseminated information, questions emerged regarding its neutrality. This study highlights the increasing influence of media and communication technologies on social movements in the digital era. Moreover, the primary issue underlying the demonstrations is government policy amid a period of political transition. The research suggests the importance of addressing how media framing shapes public perception and maintaining the public sphere as a democratic space for open discourse, free from intervention by particular political interests.